The Impact of the Covid Pandemic on UK Economic Policy and Its Legacy - Nicholas Sowels (Revue Française de Civilisation Britannique)
This article examines the economic impact of the Covid-19 pandemic on the UK in comparison to previous shocks since 1980. It details the economic measures taken by the public authorities to deal with the crisis, including massive public spending to support household incomes and powerful monetary policy measures. The analysis then looks at the economic legacies of the pandemic, especially concerning public debt and inflation, noting that at the time of the general election in July 2024 Britain’s economic outlook had stabilised and inflation had ebbed. However, the article concludes that the era of unprecedented ultra-low interest rates which began in the wake of the global financial crisis (2007-2009) is over. It emphasises that while today’s high public debt is not unprecedented in British history it will weigh heavily on public spending in the years, if not decades, to come.